Enhanced chromium removal from tannery wastewater through electrocoagulation with iron electrodes: Leveraging the Box-Behnken design for optimization - Aguilar Ascón E. (2024)
This study is focused on reducing total chromium level in tannery wastewater through the electrocoagulation process, in order to comply with the maximum permissible limits (MPL) and to determine the effects from its main operating factors. For this purpose, a batch electrocoagulation reactor was manufactured using iron electrodes. Next, the response surface methodology was applied in the experimental design using a Box–Behnken design (BBD) with three factors: current intensity, treatment time, and level. In addition, the total chromium removal percentage was taken as a response variable.